A New 3D Statistical Parameter for Determining Roughness of Joint Surfaces Considering Shear Direction and Asperity Features - Liu, Juan; Gao, Feng; Xing, Yan; Zheng, Wenqi; Bai, Yun (KSCE journal of civil engineering, 2023)
The engineering rock mass is a multi-fracture body crisscrossed by geologic structure planes, and its safety is affected by the rock joints’ mechanical properties and morphological features. The joint roughness coefficient ( JRC ) is a vital characterization method to describe joint surface roughness. Its precise quantization is a crucial factor in predicting shear strength. However, JRC in recent research did not reflect the directional effect of the joint morphology. A new 3D roughness parameter WAD (weighted apparent dip) was proposed to estimate JRC based on the apparent dip angle of the contact unit. The proposed parameter comprehensively reflects the contribution of shear direction and asperity features to the roughness. Based on the ten standard roughness profiles, we investigated the directionality of the WAD and studied the influence of the sampling interval ( S ai ) on WAD and their correlation with JRC . And the practicability of WAD in evaluating JRC was well verified by the comparison between the indoor test and calculated results with different roughness and shear directions, and the results showed that WAD could accurately estimate the shear strength of the joint rock.